Zoledronic acid causes γδ T cells to target monocytes and down‐modulate inflammatory homing. Issue 4 (December 2014) - Fowler, Daniel W.; Copier, John; Dalgleish, Angus G.; Bodman‐Smith, Mark D.
Summary Zoledronic acid (ZA) is a potential immunotherapy for cancer because it can induce potent γδ T‐cell‐mediated anti‐tumour responses. Clinical trials are testing the efficacy of intravenous ZA in cancer patients; however, the effects of systemic ZA on the activation and migration of peripheral γδ T cells remain poorly understood. We found that γδ T cells within ZA‐treated peripheral blood mononuclear cells were degranulating, as shown by up‐regulated expression of CD107a/b. Degranulation was monocyte dependent because CD107a/b expression was markedly reduced in the absence of CD14+ cells. Consistent with monocyte‐induced degranulation, we observed γδ T‐cell‐dependent induction of monocyte apoptosis, as shown by phosphatidylserine expression on monocytes and decreased percentages of monocytes in culture. Despite the prevailing paradigm that ZA promotes tumour homing in γδ T cells, we observed down‐modulation of their tumour homing capacity, as shown by decreased expression of the inflammatory chemokine receptors CCR5 and CXCR3, and reduced migration towards the inflammatory chemokine CCL5. Taken together our data suggest that ZA causes γδ T cells to target monocytes and down‐modulate the migratory programme required for inflammatory homing. This study provides novel insight into how γδ T cells interact with monocytes and the possible implications of systemic use of ZA in cancer.